An Intelligent Vehicular Accident Notification System - Rasmi, M; Harishma, CM (International Journal of Computer Sciences and Engineering, 2025)
Road safety is one of the main objectives on designing the assistance system. Nowadays everyone needs to have a safer transport. Even if any accident happens, no one take cares about it. A large number of precious lives are lost due to road traffics accidents every day. There is need to have effective road accident detection and information communication system in place to injured persons. The proposed system helps to identify the accidents in remote areas with the help of smart phone. It uses a vibration sensor which detects the variation of the vibration system, and makes a message to transfer the details about the location of accident to contacts .So we can save the life of people